Toluene Conversion by Using Different Morphology MnO2 Catalyst - Huaijian Wang; Fangtong Liu; Wenting Yang; Chenglong Yu; Huanhuan Xiong; Jiaqi Li; Meijuan Lu (Aerosol and Air Quality Research)
Abstract MnOx was one of the important catalysts for the degradation of organic compounds. MnO2 with different morphology (nanotube, nanowire, nanocubic and nanoflower) were synthesized by hydrothermal method using KMnO4 and MnSO4 as precursors. Firstly, their structures were studied by X-ray diffraction (XRD), N2 adsorption desorption curve, H2 temperature programmed reduction (H2-TPR) and X-ray electron spectroscopy (XPS). Next, their catalytic conversion test for toluene was carried out under the condition of toluene concentration of 500 ppm and gas flow rate of 200 mL min−1. The results showed that the crystal structure of nanotube and nanowire were α-MnO2, nanoflower was α-MnO2 phase and other crystalline, the nanocube was β-MnO2. For the different morphology MnO2, their catalytic conversion activity for toluene were increased with the rise of temperature. Nanotube, nanowire, nanoflower and nanocube reached 100% toluene conversion at 225°C, 250°C, 275°C and 325°C, respectively. MnO2 nanotube showed the highest activity for toluene among all the samples, which attribute to the larger specific surface area, better low-temperature reduction performance and higher the Mn4+ content.